Corporate Training of Yakutia Teachers to Apply Methods of E-Learning - Anatolyevich Sorochinsky, Maxim (2020)
Teacher training can assist in initiating digital changes in education. However, to achieve this, the training should use leading examples from the field of digital education solutions and technologies, while university and school educators should be trained to apply them in their work and to create high-tech educational startups in the field of e-learning. The goal of this study was to increase the professional competencies of teachers by conducting a corporate course that would prepare the teachers of the university in Yakutia to apply e-learning methods. The article demonstrates that the introduction of e-learning at the university is an important comprehensive process that implies transformation of all education components under the influence of modern technologies. Its practical implementation requires changing the goals, organizational forms, and technologies of educational activities in line with new technologies as well as the development of productive strategies for integrating the created innovations into the traditional learning process. For this purpose, the authors conducted a sociological study that helped identify the main problems associated with this type of training (for example, developing a course is time-consuming and a lack of required skills to develop courses). Based on the obtained data, the authors proposed a corporate course for university teachers on the creation of educational content for e-learning. It was shown that when applying new types of educational activities, teachers should combine traditional and new technologies, which contributes to the innovative training of teachers to meet the requirements of the digital society. This study focused on practical issues, since the research results were implemented in the work of the North-Eastern Federal University (NEFU), the base of the research. The results can be used when training teachers to apply e-learning methods in other educational institutions.